Comparative Analysis of Koninklijk Nederlandsch-Indisch Leger (KNIL) and Pembela Tanah Air (PETA) Military Training as Precursors to the Indonesian National Armed Forces - Utama, Taqwa Ridlo (The Republic of Indonesia Defense University, 2024)
The Indonesian National Armed Forces (TNI) were formed from three groups with different training backgrounds: those trained by the Dutch, Japanese, and civilian militias. Only the first two groups underwent professional military training. The Dutch military trained the first group as part of the Koninklijk Nederlandsch-Indisch Leger (KNIL), and the second group received military training from the Japanese while being part of the Volunteer Army for the Defence of the Homeland (Pembela Tanah Air or PETA). This article conducts a comparative analysis of the military training received by soldiers from KNIL and PETA. It examines the aspects that differentiate the training of these two armed forces, which served as the foundation for the Indonesian military. This research approach uses historical methods and sociological analysis. The study utilizes primary and secondary sources, with primary sources as the main references. These primary sources were obtained by examining contemporary newspaper records and autobiographical notes from individuals who underwent training in KNIL and PETA. Notable newspaper sources include Asia Raya, Bataviaasch Nieuwsblad, De Sumatra Post, Kan Po, and Soerabaiasch Handelsblad. The findings revealed significant differences between the KNIL and PETA training programs, which can be classified into technical training and training culture. Technical training differences included divisions, recruitment, classification, duration, and content. Training culture differed as KNIL adopted Western military professionalism, emphasizing separation from civilian life. In contrast, PETA adopted the Japanese bushido doctrine and the Remarkable Trinity concept, emphasizing harmony between the military, government, and people. This study concludes that the training and frameworks established by both groups played a crucial role as precursors to the TNI.